Use of Remotely Piloted Aircraft (RPA) in the estimation of sea lion populations in south Chincha Island – Ica - Brondi Rueda, Nestor (2020)
This paper describes the use of RPA technology as a complementary method during Southern sea lions (Otaria flavescens) counting in Chincha Sur Island, Ica – Peru, as part of the activities scheduled by the Instituto del Mar del Perú (IMARPE). Colonies of these pinnipeds were mapped and its subsequent classification in the Systems of Geographic Information was carried out in order to make comparisons between direct counting on the field and RPA mapping counts. Total values by direct counting and orthophotos were 2300 and 2700 individuals, respectively. While no significant differences were found between the two methods, by means of digital counting, a better detail of the number of individuals on the females and pups categories could be achieved. The use of RPA constitutes a valuable tool that provides geographical reference of each individual and enables repetitions of the counts by different people.